The art of metaphore in the poems of baderkhan sindi’s divan (hozanet min) as a model - IBRAHIM AHMED, DILDAR; KHORSHEED ABDULLAH, HALEEMA; YOUSIF IBRAHIM, ARAM (Journal of Duhok University, 2019)
The metaphor is the main focus of this research and metaphor in terms of language taking something from me something else, while in terms of the conversion of meaning from one word to another in the presence of analogy in its hidden structure and the importance of metaphor in the approximation qualities of the subject to be stronger impact on the self and the performance of rhetorical expression and create a new image. The metaphor is one of the main rhetoric arts which fall within the framework of rhetorical arts. This art is used extensively for the construction of the poetic language, where poetry schools of various kinds rely on metaphors in order to build their literary language. The poet Badrakhan Sindi belongs to any modern poetical school, a great echo in the literary circles, especially in the province of Dohuk, is a poet who adopted the arts of rhetoric to the systems of their logo, especially the art of metaphor. This study is devoted to the identification and analysis of the art of metaphor in his poetry, and this is to show how the use of this graphic art of various kinds in his poetry. The study was based on its identified debt (hozanit min) of Badrakhan Sindi. Through the study was identified metaphors and hidden metaphor in various types of poetry. This study is described as "the art of borrowing in the poems of Badrakhan Sindi Diwan, (Hozanit Min) as a model, an attempt to determine the art of borrowing in his poet’s.